Photoluminescent Patterned Papers Resulting from Printings of Polymeric Nanoparticles Suspension - Pierre Sarrazin; Davide Beneventi; Aurore Denneulin; Olivier Stephan; Didier Chaussy (International Journal of Polymer Science)
The printability of a copolyfluorene-fluorenone (PFFO) photoluminescent nanoparticle aqueous suspension on commercial tracing paper was here investigated. The nanoparticles suspension was obtained by miniemulsification of a suitable preformed photoluminescent organic polymer. The structural, physicochemical, and rheological characteristics of the nanoparticles suspension were first studied before considering its printability by inkjet and flexography techniques. The native properties of the nanoparticles suspension revealed to be more suitable for inkjet printing which was successfully used to print photoluminescent patterns using a very low amount of PFFO.